2013
DOI: 10.1097/tp.0b013e3182a1cd0c
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Overgrowth in Renal Transplant Subjects

Abstract: There was no incidence of GO, and a decrease in the occurrence and severity of GO was significant in total sample. This decrease can be attributed to changes in pharmacologic and periodontal variables over this period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…1120 Common AEs were hyperlipidemia; comparator-adjusted frequency, 21% 21 ; hypertension, 26% 22 ; cardiac events, 19% 23 ; gingival hyperplasia, 13–43% 24,25 ; and increased creatinine, 12%. 26 The incidence of AEs was not consistently shown to be dose related, and observed drug concentrations among those with certain AEs were often similar to those in patients without these events.…”
Section: Resultsmentioning
confidence: 99%
“…1120 Common AEs were hyperlipidemia; comparator-adjusted frequency, 21% 21 ; hypertension, 26% 22 ; cardiac events, 19% 23 ; gingival hyperplasia, 13–43% 24,25 ; and increased creatinine, 12%. 26 The incidence of AEs was not consistently shown to be dose related, and observed drug concentrations among those with certain AEs were often similar to those in patients without these events.…”
Section: Resultsmentioning
confidence: 99%
“…As a potent immunosuppressant, cyclosporin A (CsA) has been used for the prevention of transplant rejection or treatment of rheumatoid arthritis. Around 50% of adult transplant patients may encounter CsA-associated gingival enlargement [ 85 , 86 ]. It was suggested that administration of CsA may induce EMT in gingival epithelium [ 62 ], and the upregulation of the EMT inducer Slug was observed in HGFs [ 64 ].…”
Section: Gingival Overgrowthmentioning
confidence: 99%
“…Some immunosuppressants such as cyclosporine A and, according to some authors, tacrolimus are also associated with gingival enlargement. 53 , 139 Proper periodontal maintenance is necessary to avoid the appearance of gingival enlargement. Despite proper periodontal control, gingival enlargement may appear around the implants.…”
Section: Dental Implant Treatmentmentioning
confidence: 99%